Human papillomavirus type 16 E7 perturbs DREAM to promote cellular proliferation and mitotic gene expression - DeCaprio, James A. (2013)
Study of the small DNA tumor viruses continues to provide valuable new insights into oncogenesis and fundamental biological processes. While much has already been revealed about how the human papillomaviruses (HPVs) can transform cells and contribute to cervical and oropharyngeal cancer, there clearly is much more to learn. In this issue of Oncogene, Pang et al. demonstrate that the high-risk HPV16 E7 oncogene can promote cellular proliferation by interacting with the DREAM (DP, RB-like, E2F and MuvB) complex at two distinct phases of the cell cycle (1). Consistent with earlier work, HPV16 E7 can bind to the retinoblastoma tumor suppressor (RB) family member p130 (RBL2) protein and promote its proteasome-mediated destruction thereby disrupting the DREAM complex and prevent exit from the cell cycle into quiescence. In addition, they demonstrate that HPV16 E7 can bind to MuvB core complex in association with BMYB and FOXM1 and activate gene expression during the G2 and M phase of the cell cycle. Thus, HPV16 E7 acts to prevent exit from the cell cycle entry and promotes mitotic proliferation and may account for the high levels of FOXM1 often observed in poor risk cervical cancers.